2016
DOI: 10.1093/mnras/stw3344
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a soft X-ray 8 mHz QPO from the accreting millisecond pulsar IGR J00291+5934

Abstract: In this paper, we report on the analysis of the peculiar X-ray variability displayed by the accreting millisecond X-ray pulsar IGR J00291+5934 in a 80 ks-long joint NuSTAR and XMM-Newton observation performed during the source outburst in 2015. The light curve of the source was characterized by a flaring-like behavior, with typical rise and decay time scales of ∼120 s. The flares are accompanied by a remarkable spectral variability, with the X-ray emission being generally softer at the peak of the flares. A st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…For example, different composition of the burning material, different accretion geometry (i.e., accretion mainly onto the NS equator vs. spherical accretion onto most of the NS surface), different NS spin frequency and/or magnetic field, and a combination of all these, can affect the burning process and how we detect it. Ferrigno et al (2017) detected a QPO at an approximately constant frequency of ∼ 8 mHz in the accreting millisecond X-ray pulsar (AMXP) IGR J00291+5934. The QPO was persistently present during an 80-ksec XMM-Newton observation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, different composition of the burning material, different accretion geometry (i.e., accretion mainly onto the NS equator vs. spherical accretion onto most of the NS surface), different NS spin frequency and/or magnetic field, and a combination of all these, can affect the burning process and how we detect it. Ferrigno et al (2017) detected a QPO at an approximately constant frequency of ∼ 8 mHz in the accreting millisecond X-ray pulsar (AMXP) IGR J00291+5934. The QPO was persistently present during an 80-ksec XMM-Newton observation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, two harmonically related QPOs are observed at ∼ 20 mHz and ∼ 40 mHz that appear more like the low-frequency QPOs observed in black holes (Linares et al 2007) than any feature normally seen in accreting neutron stars. The 2015 outburst showed a similar band-limited noise structure, but different QPOs (Ferrigno et al 2017). In that outburst a prominent 8 mHz QPO was observed at low (< 2 keV) energies.…”
Section: Igr J00291+5934mentioning
confidence: 72%
“…We can distinguish two instances of mHz QPOs, namely the 8 mHz QPO observed with XMM-Newton in the 2015 outburst (Ferrigno et al 2017) and the ∼ 20 mHz and its harmonics as seen in RXTE observations of earlier outbursts (Linares et al 2007;Hartman et al 2011). Because the two versions of millihertz variability are not observed simultaneously, nor in the same energy band, it is unclear if they share the same underlying physical mechanism (Ferrigno et al 2017). In the following we therefore first discuss the XMM-Newton and RXTE results separately, before briefly considering them together.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This feature is not seen MAXI J0911, but if it is due to 'heartbeat' variability (Belloni et al 2000;Altamirano et al 2011), as suggested by Ferrigno et al (2017), then such flaring may be a transient phenomenon and MAXI J0911 may in fact be a good candidate to monitor for such variability.…”
Section: Igr J00291+5934mentioning
confidence: 99%